Cd2+‐induced Fluorescent Metallogel: A Case of CHEF and ACQ Phenomena. Issue 13 (22nd June 2022) - Dixit, Manish Kumar; Mahendar, Chinthakuntla; Dubey, Mrigendra
Abstract: A fluorescent metallogel (1 %w/v) has been synthesized from deprotonation of a non‐fluorescent adipic acid‐derived ligand H2 AL with LiOH followed by coordination with Cd 2+ in DMF. Cd 2+ not only induces the coordination complex formation but also leads to aggregation, formation of nanofibers of about ≈12 nm average diameter and gelation. The metallogel was also found to be reversibly stimuli‐responsive towards heating and mechanical shaking whereas it was resistant to ultrasound. The involvement of chelation‐enhanced fluorescence (CHEF), aggregation‐induced emission (AIE) and aggregation‐caused quenching (ACQ) during the course of gelation has been well established by fluorescence experiments. Further, the coordination complex involved in metallogel formation has been well characterized by ESI‐MS and Job's plot. The synthesized metallogel has a true gel phase as shown by detailed rheological studies. The mechanism of gelation is well established by using FTIR, UV‐vis, fluorescence, lifetime measurement, Job's plot, ESI‐MS, PXRD and TEM techniques. Abstract : An adipic acid‐derived ligand H2 AL for the synthesis of a Cd 2+ coordination‐based fluorescent metallogel has been reported. Three fluorescence phenomena, that is, chelation‐enhanced fluorescence (CHEF), aggregation‐caused quenching (ACQ) and aggregation‐induced emission (AIE), were involved during the course of gelation.